Strengthening and sustaining vitality of urban areas: the case of North-West India - Teotia, Manoj Kumar (2007)
In the states of north-west India - Punjab, Haryana and Himachal Pradesh - and the Union Territory of Chandigarh, the urban areas are growing with serious deficiencies in infrastructure, housing, civic services, environmenty and governance. This article highlights the challenges that the urban areas of north-west India are facing and to see their short-term as well as long-term implications. an attempt has also been to suggest alternative strategies and innovations to meet the urban challenges. - Reproduced.
Keywords: Urban development